Chlorpheniramine Maleate Pediatric Oral Strip: Methodology and Characterization - Sura Zuhair Mahmood; Hiba Sabah Sabry; Nora Zawar Yousif; Zeina D. Salman (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Objective: The goal of performing this study is to prepare an oral strip, especially designed for pediatric use that provides fast onset of action with ease of swallowing particularly for young individuals who suffer from difficulty of swallowing, in addition provides maximum therapeutic effectiveness by reducing the first pass effect. Materials and methods: The oral strip was prepared by solvent casting technique through using different sole polymers (hydroxypropyl methylcellulose [HPMC] 15cp, HPMC 50cp, polyvinyl alcohol, and sodium carboxymethyl cellulose). Maltodextrin (MD) was added as the secondary polymer in different ratios to optimize the release parameters, and disintegration time (DT), three different plasticizers were employed (propylene glycol, dibutyl phthalate, and glycerin) to boost the film forming polymer characteristics. Results: From this study, it is obvious that F10 which composed of HPMC as a main polymer and MD as a secondary polymer in ratio 2:1, respectively, provides adequate physicochemical characteristics, in-vitro/ in-vivo DT (40/36 s), respectively, nevertheless a satisfactory release parameter as (59.9%) released at 2 min and 80% of drug released at 14.8 min. Conclusion: The optimized formula is pretty encouraging to originate an oral strip that provides ease of administration, fast onset of action with wide acceptance for the pediatric population.